El arbitraje laboral en el sector estatal - Arévalo Vela, Javier (2023)
Based on a study of the law and case law concerning collective labor relations, this document describes the types of collective bargaining at the centralized and decentralized levels in the public sector, analyzing arbitration as an alternative to settle economic labor disputes. After describing the structure of the arbitration award and its execution, it is concluded that it is a mistake to grant executory force to an arbitration award derived from a public collective bargaining, since it does not recognize a certain and enforceable obligation in favor of a worker, but general obligations in favor of a group of workers.